Radiotherapy after breast‐conserving surgery for elderly patients with early‐stage breast cancer: A national registry‐based study. Issue 4 (14th September 2020) - Wang, Fei; Meszoely, Ingrid; Pal, Tuya; Mayer, Ingrid A; Bailey, Christina E.; Zheng, Wei; Shu, Xiao‐Ou
Abstract: Considerable controversies exist regarding whether elderly patients with early‐stage breast cancer receiving breast‐conserving surgery (BCS) should forgo radiotherapy. We utilized the National Cancer Database to analyze data of 115 516 women aged ≥70 years, treated with BCS for T1‐2N0‐1M0 breast cancer between 2004 and 2014. Multivariable Cox proportional hazards model was used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for mortality 3, 5 and 10 years after 90 days of BCS associated with radiotherapy. Patients who received no radiotherapy had a higher mortality rate than those who received radiotherapy (5‐year survival rate: 71.2% vs 83.8%), with multivariable‐adjusted HRs of 1.65 (95% CI: 1.57‐1.72) for 3‐year mortality, 1.53 (1.47‐1.58) for 5‐year mortality and 1.43 (1.39‐1.48) for 10‐year mortality. The association held even for patients ≥90 years. This association was observed in all strata by reasons for radiotherapy omission, receipt of endocrine therapy or chemotherapy, calendar period and other clinical characteristics, with 40% to 65% increased 5‐year mortality for patients without radiotherapy. This positive association persisted when analyses were restricted to patients with T1N0 and estrogen‐receptor‐positive disease who had received endocrine therapy (5‐year mortality: HR 1.47 [1.39‐1.57]) and in propensity score weighted analyses. Our study shows, in routine practice, elderly patients who received no post‐BCS radiotherapy had higher total mortality than those who received radiotherapy. These findings suggest that the current recommendation of omission of post‐BCS radiotherapy for elderly women with early‐stage breast cancer may need to be reconsidered, particularly for those without contraindication. Abstract : What's new? Radiotherapy following breast conserving surgery (BCS) is the standard‐of‐care for women diagnosed with early‐stage breast cancer. For women over age 70, however, radiotherapy after BCS is controversial. This analysis of data from the U.S. National Cancer Database identifies an association between radiotherapy omission and increased mortality among women age 70 or older who received BCS. The association was detectable even among patients with early‐stage, estrogen receptor‐positive breast cancer who underwent endocrine therapy. Hence, radiotherapy omission may not be uniformly beneficial for elderly women with early‐stage breast cancer. Further investigation is warranted to identify prognostic factors to guide indiviualized radiotherapy in this elderly population.